Gender and critical media-information literacy in the digital age: Kenya, South Africa and Nigeria. (1st September 2016) - Mudhai, Okoth Fred; Wright, Bianca; Musa, Aliyu
In 1985 Kenya hosted the UN World Congress on Women to tackle gender-based violence (GBV) and enhance women's standing generally, but recently, in 2014, the country experienced a wave of public stripping of women – some captured on video and distributed via social media. These human rights violations, especially in Nairobi, happened in a nation that has witnessed three decades of pro-women activism bloom and whose constitution prescribes gender equity, with recent laws toughening punishment for sexual offences. Yet similarly worrying waves of GBV have occurred in other African countries. Focusing on Kenya, South Africa and Nigeria, we use constructivist theory of framing and discourse analyses of media and interview texts to examine the extent to which purposively selected digital era change agents use mainstream and social media to aid critical literacy in their capacitybuilding bid to alter retrogressive attitudes harmful to women's rights and progress.